2008
DOI: 10.2174/1874143600802010063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of a Cissus verticillata Fraction and Tyramine, its Bioactive Constituent, on Alloxan-Induced Diabetic Rats

Abstract: In the present study, the antioxidant activity of a methanol soluble fraction (MSF) from Cissus verticillata, used in Brazil and elsewhere as a hypoglycemic and antidiabetic medicinal plant, and tyramine (TYR), one of its main bioactive constituents, was assessed. For this, male Wistar rats were submitted to alloxan injection (40 mg/kg, i.v.) in order to induce a diabetic state and, 48 h later, glycemia was determined. Animals were distributed into groups: normal controls (NC); diabetic controls (DC); DC plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A methanol fraction containing Tyramine obtained from a lyophilised aqueous extract of C. verticillata shows antioxidant activity on Alloxan-induced diabetic rats as reported by Viana et al 10 .…”
Section: Introductionmentioning
confidence: 58%
“…A methanol fraction containing Tyramine obtained from a lyophilised aqueous extract of C. verticillata shows antioxidant activity on Alloxan-induced diabetic rats as reported by Viana et al 10 .…”
Section: Introductionmentioning
confidence: 58%
“…The highest radical scavenging effect was observed in the stem extract with IC 50 of 29.25 µg/mL. 26 The ethanol extract of Cissus quadrangularis was used as anti-osteoporotic activity. It worked on healthy albino rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to possess various biological properties, such as antioxidant 5 , a 1 -adrenergic agonistic 6 and monoamine oxidase 7 . It is reported that administration of tyramine to diabetic rats reduces the hyperglycemia, even at doses that have low effects on cardiovascular variables 8 . The synthesis of imines or Schiff's bases has special significance in organic synthesis and medicinal chemistry 9 .…”
mentioning
confidence: 99%